Apresentação do Dossiê - Barbosa, Ana Angélica Leal; Eugenio, Benedito; Oliveira, Iris Verena; Dutra, Nivaldo Osvaldo (ODEERE, 2020)
Apresentação do Dossiê QUILOMBOS: RESISTÊNCIAS E RESSIGNIFICADOS NA CONTEMPORANEIDADE